Malignant melanoma treatment using brachytherapy: Two case reports and 15 case series. Issue 1 (4th October 2022) - Ishiguro, Akihiro; Ogata, Dai; Okuma, Kae; Kashihara, Tairo; Murakami, Naoya; Hiki, Kojiro; Yamakawa, Kohei; Jinnai, Shunichi; Takahashi, Akira; Namikawa, Kenjiro; Igaki, Hiroshi; Yamazaki, Naoya
Abstract: Malignant melanoma (MM) is usually resistant to radiotherapy. Brachytherapy may be an option in patients with bleeding or pain, and those in whom surgery is difficult. Brachytherapy has few side effects and can be used in combination with external beam radiotherapy or chemotherapy. We summarize the demographic and clinical characteristics of 15 patients who received brachytherapy for MM at our hospital and describe two of these representative cases. Patient 1 had an approximately 10‐mm, dark‐red nodule near the external urethral meatus. Excision was not performed to preserve urethral function. A gradual improvement was observed after 48 Gy of remote afterloading system (RALS) brachytherapy and nivolumab therapy. Patient 2 had a 38‐mm, black tumor on the vagina. Post‐resection, RALS brachytherapy was administered to treat the residual black macule and a lesion quickly disappeared. In all 15 cases, nine patients received radiotherapy for local control and six patients received palliative radiotherapy to reduce symptoms such as bleeding and pain. The irradiation site was the vagina in six patients, lymph node metastasis in five, head and neck in two, skin or subcutaneous metastases in two, and the anus in one. Treatment effect for local control and palliative care was 75% and 83% of patients, respectively. In particular, disappearance of the tumor or disappearance of symptoms was observed in half of the cases of brachytherapy to the vagina. On the other hand, brachytherapy was not very effective for lymph node metastases. Immediately after radiotherapy, eight (53%) patients experienced dermatitis or mucositis. Due to the histological and structural characteristics of mucosal melanoma of the luminal organs, brachytherapy may be an effective therapy. Hence, widespread use of brachytherapy with an appropriate irradiation technique aiming for local control and palliative care in case of unresectable MM should be considered.